Respuesta :
The equation of the tangent to the curve at θ = 0 is y = (3x + 1)/2
To find the equation of the tangent, we need to find dy/dx ,the tangent to the curve.
So, dy/dx = dy/dθ ÷ dx/dθ
Finding dy/dθ
Since y = sin(3θ) + cos(2θ)
dy/dθ = d[sin(3θ) + cos(2θ)]/dθ
dy/dθ = dsin(3θ)/dθ + dcos(2θ)/dθ
dy/dθ = 3cos(3θ) + [-2sin(2θ)]
dy/dθ = 3cos(3θ) - 2sin(2θ)
Finding dx/dθ
Also, x = cos(3θ) + sin(2θ)
dx/dθ = d[cos(3θ) + sin(2θ)]/dθ
dx/dθ = dcos(3θ)/dθ + dsin(2θ)/dθ
dx/dθ = -3sin(3θ) + 2cos(2θ)
dx/dθ = 2cos(2θ) - 3sin(3θ)
Finding dy/dx
So, dy/dx = dy/dθ ÷ dx/dθ
dy/dx = 3cos(3θ) - 2sin(2θ) ÷ [2cos(2θ) - 3sin(3θ)]
when θ = 0
dy/dx = 3cos(3 × 0) - 2sin(2 × 0) ÷ [2cos(2 × 0) - 3sin(3 × 0)]
dy/dx = 3cos(0) - 2sin(0) ÷ [2cos(0) - 3sin(0)]
dy/dx = 3 × 1 - 2 × 0 ÷ [2 × 1 - 3 × 0]
dy/dx = 3 - 0 ÷ [2 - 0]
dy/dx = 3/2
We now find the values of y and x when θ = 0.
Finding the value of y
So, y = sin(3θ) + cos(2θ)
y = sin(3 × 0) + cos(2 × 0)
y = sin(0) + cos(0)
y = 0 + 1
y = 1
Finding the value of x
Also, x = cos(3θ) + sin(2θ)
x = cos(3 × 0) + sin(2 × 0)
x = cos(0) + sin(0)
x = 1 + 0
x = 1
Finding the equation of the tangent
We now find the tangent to the curve from (y - y₀)/(x - x₀) = dy/dx
So, with x₀ = 1, y₀ = 1 and dy/dx = 3/2, we have
(y - y₀)/(x - x₀) = dy/dx
(y - 1)/(x - 1) = 3/2
y - 1 = 3/2(x - 1)
y = 3x/2 - 1/2 + 1
y = 3x/2 + 1/2
y = (3x + 1)/2
So, the equation of the tangent to the curve at θ = 0 is y = (3x + 1)/2
Learn more about equation of tangent to curve here:
https://brainly.com/question/7252502